Globallashuv davrida milliy qadriyatlarni asrab-avaylashning muhim jihatlari - Majidova Zebiniso Salohiddin qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This thesis discusses the importance and significance of preserving national values in the context of the deepening process of globalization in today's world. It addresses the necessity not only to preserve these values but also to develop them, and outlines the system of actions that should be implemented to achieve this goal.